OP01 Withdrawal of infliximab or anti-metabolite therapy in Crohn's Disease patients in sustained remission on combination therapy: A randomized unblinded controlled trial (SPARE). (21st January 2022) - Louis J, E; Resche-Rigon, M; Laharie, D; Satsangi, J; Ding, N; Preiss, J; D'Haens, G; Picon, L; Bossuyt, P; Vuitton, L; Irving, P; Bouhnik, Y; et al.
Abstract: Background: Combination therapy with infliximab and anti-metabolites is a standard option for patients with Crohn's disease (CD). The implications of long term use of combination therapy may lead patients and clinicians to contemplate treatment de-escalation once steroid-free remission has been achieved. The aim of our study was to assess the relapse rates and time spent in remission over 2 years, after withdrawal of infliximab or anti-metabolite compared to continuation of combination therapy. Methods: CD patients treated with a combination therapy of infliximab (IFX) and anti-metabolite > 8 months and in sustained steroid-free remission > 6 months were recruited in 64 centers in France, United Kingdom, Belgium, Sweden, Australia, Germany and The Netherlands. Patients were randomized into 3 arms - continuing combination therapy (arm A); stopping IFX (arm B); or stopping anti-metabolite (arm C). In case of a relapse [defined by CDAI and an objective marker of inflammation (CRP or fecal calprotectin)], patients were retreated by resuming infliximab in arm B or the anti-metabolite in arm C, according to a pre-defined scheme, including optimization of IFX up to 10 mg/Kg if necessary in all arms. The two co-primary endpoints were the relapse rate and mean survival time spent in remission over 2 years. A major secondary endpoint was treatment failure (complications or not recapturing remission). Results: 254 patients were screened, 211 randomized, 5 withdrew consent and 1 was lost to follow-up, leaving 205 patients for the analysis - 67 randomized to arm A, 71 to arm B and 67 to arm C. Demographic and clinical characteristics are shown in Table 1. The two-year relapse rates were 14% (IC95%: 4–23%) in arm A, 40% (IC95%: 28–51%) in arm B, and 10% (IC95%: 2–18%) in arm C (p=0.0003 arm B vs arm A and <0.0001 arm B vs arm C) (figure 1). The time spent in remission was 1.91 yrs (IC95%: 1.83–1.99), 1.89 yrs (IC95%: 1.82–1.96) and 1.93 yrs (IC95%: 1.86–2.00) in arm A, B and C, respectively. Out of the 39 relapsers, 28 were retreated/optimized. Remission was achieved in 1/2 retreated patients in arm A, 22/23 in arm B and 2/3 in arm C. Treatment failure was observed in 4/67, 4/71 and 3/67 patients, in these three arms, respectively. No malignancy was observed, one tuberculosis in arm C and two severe infections (pneumonia and viral pericarditis) in arm B. Conclusion: Infliximab withdrawal, but not antimetabolite withdrawal, was associated with a significantly higher risk of relapse than continuation of combination therapy. Almost all patients who stopped IFX achieved rapid remission when resuming treatment. The time spent in remission over 2 years was similar across groups.